2019
DOI: 10.3892/etm.2019.7307
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PRINS is involved in the development of nephropathy in patients with diabetes via interaction with Smad7

Abstract: Long non-coding RNA psoriasis-susceptibilityrelated RNA gene induced by stress (PRINS) is known to be involved in kidney ischemia reperfusion injury. The aim of the current study was to investigate the potential role of PRINS in diabetic nephropathy. The relative mRNA expression level of PRINS and SMAD family member 7 (Smad7) was examined in patients with diabetes, including patients without obvious complications (n=43), patients with diabetic nephropathy (n=33), diabetic retinopathy (n=37), diabetic cardiomyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Moreover, the up-regulation of PRINS in psoriatic non-lesional epidermis induced the expression of anti-apoptotic G1P3 protein and caused the hyperproliferation of keratinocytes [ 36 ]. PRINS is also connected with the development of nephropathy in patients with diabetes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the up-regulation of PRINS in psoriatic non-lesional epidermis induced the expression of anti-apoptotic G1P3 protein and caused the hyperproliferation of keratinocytes [ 36 ]. PRINS is also connected with the development of nephropathy in patients with diabetes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA PRINS was obviously increased in patients with DN and lncRNA PRINS overexpression declined the viability of mouse podocyte cells. 14 Studies have shown that lncRNA KCNQ1OT1 expression is increased in patients with diabetic cardiomyopathy, and KCNQ1OT1 interference can reduce the functional damage to diabetic cardiomyocytes and the pyroptosis of cells. 15,16 Mary E. Travers et al have demonstrated that CDKN1C, KCNQ1, and KCNQ1OT1 are possibly mediate diabetes susceptibility at the KCNQ1 locus and mediate the diabetes risk in early development.…”
Section: Introductionmentioning
confidence: 99%
“…Several lncRNAs, such as lncRNA MALAT1 [ 25 ] and lncRNA PRINS [ 26 ], have been found to be involved in the development of DN, they regulated mRNA expression at the post-transcriptional level. In this study, we found that CASC2 expression was prominently down-regulated in high glucose-stimulated podocytes in a time-dependent manner and dose–response manner.…”
Section: Discussionmentioning
confidence: 99%